Writing Back: Ethics and Aesthetics in Joss and Gold - Sankaran, National University of Singapore, Chitra (Asiatic: IIUM Journal of English Language and Literature, 2014)
Shirley Geok-lin Limâ€™s novel, Joss and Gold, published in 2001, can be viewed as quintessentially â€œacademicâ€ in some ways because, though it has an intricate plot and a well-paced narrative, it also raises all the pertinent questions that are the central preoccupations of resistance discourses such as feminism and post-colonialism. My paper will examine how these resistant discourses emerge in the text and the ways in which the novel writes back to a western tradition that has typecast Asia in general and Asian women in particular. I examine some of the ethical concerns and aesthetic designs that emerge and discuss how characterisation, plot and thematic concerns push forward ethical agendas. I also discuss how the ethical and aesthetic dimensions meld into each other in order to foreground issues that are central to the debate, such as the construction of the modern Asian woman, the concept of the nation and so forth.